Integrating Internal Audit Determinants for Enhancing Organizational Sustainability: A Systematic Literature Review - Sadia Islam; Nusrat Jahan; Dr. Md. Saheb Ali Mondal; Nazma Akter (International Journal of Financial, Accounting, and Management, 2026)
Purpose: This study aims to develop a conceptual synthesis of internal audit determinants that contribute to organizational sustainability. Research Methodology: A Systematic Literature Review (SLR) approach was employed to examine 85 peer-reviewed articles published between 2016 and 2026. Relevant studies were retrieved from major academic databases, including Taylor and Francis, Springer, SAGE, MDPI, Emerald, and Google Scholar. Results: Key internal audit determinants, including audit quality, competence, independence, ethical conduct, governance, management support, training, experience, and risk management capability, were frequently associated with organizational sustainability. Audit quality, competence, and independence emerged as dominant factors. Agency, contingency, institutional, and stakeholder theories were the most commonly applied perspectives. Regional, sectoral, and institutional differences influenced the relationships. Conclusions: This review confirms that internal audit determinants play a significant role in strengthening governance mechanisms and supporting sustainable organizational performance. A conceptual framework is proposed to illustrate the relationship between internal audit determinants and sustainability. Limitations: This study considered only English-language peer-reviewed journal articles published between 2016 and 2026, which may limit the generalizability of the findings. Contributions: This study contributes to the literature by integrating fragmented research on internal audit determinants, identifying key determinants influencing sustainability, and proposing a conceptual framework that provides a foundation for future empirical research and policy development in governance and sustainability issues.